Designing Calcium Phosphate Nanoparticles with the Co-Precipitation Technique to Improve Phosphorous Availability in Broiler Chicks - Diana A. Gutiérrez-Arenas; Manuel Cuca-García; Miguel A. Méndez-Rojas; Arturo Pro-Martínez; Carlos M. Becerril-Pérez; Maria Eugenia Mendoza-Álvarez; Fidel Ávila-Ramos; Jacinto Efrén Ramírez-Bribiesca (Animals, 2021)
Dicalcium phosphate (DP) is a mineral involved in the metabolism and development and is used as a dietary source of phosphorus (PT) for poultry. Our study objective is to design nano-dicalcium phosphate (NDP) by co-precipitation. The methodological procedure was divided into two phases: (1) NDP synthesis, and (2) bird performance, digestibility, and Ca-P in chick’s tissues. The sizes of the NDP were 20–80 nm. NDP had the Ca: P ratio of 1:1.12. The birds were divided into control diet (available P (Pa) = 0.13%) and three supplementary P sources [Commercial (Calcium phosphate), analytical grade (DP) and nanoparticles (NDP)] with three Pa levels (0.24, 0.35, 0.46%). Supplementary P sources compared to the control treatment had the highest body weight gain (698.56 vs. 228; p < 0.05) and feed intake (FI) (965.18 vs. 345.82), respectively. The digestibility of PT (67%) improved with 0.35% NDP. The highest contents of PT -breast were with the levels of 0.35 and 0.46% NDP. The PT, ash, and diameters were higher (p < 0.05) with supplementary P compared to the control treatment. As conclusion, the use of 0.35% NDP was the ideal dose in the chicks for the digestibility, absorption values, and the amount of PT in the breast.